Peran Guru Dalam Meningkatkan Numerasi dan literasisi Sekolah Dasar - Setiani, Nurul; Wakinah, Wakinah (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
Literacy is the skill of understanding reading and expressing it in written form. Numeracy is the skillof understanding, applying, and thinking about numbers and mathematical concepts in various life situations.Teachers have a role as educators, mentors, role models, and sources of knowledge for students. In addition,teachers also act as facilitators, encouragers, and inspirers in supporting students to achieve their bestabilities. This study utilizes various literature as the main source that is studied and analyzed according tothe problems or topics that have been determined, so that this research method is known as a literaturereview. The purpose of the study is the role of teachers to improve elementary school numeracy and literacy.The results are that teachers provide good examples, create a fun learning environment, are able to usetechnology, are able to patiently help students who do not understand, and provide feedback.Key words: Role Of Teachers, Literacy, Numeracy, Elementary School.